Poetycka biografia emigrantki w Opowieści o cudzoziemcach Józefy Radzymińskiej (Heteroglossia – studia kulturoznawczo-filologiczne, 2021)
The purpose of this article is to reconstruct the emigration experiences of the main characters in Jozefa Radzymińska’s poem Opowieść o cudzoziemcach and to identify points of contact with the biography of the writer herself, who lived in Argentina for fourteen years after World War II. Radzymińska described the influence of great historical processes on the lives of individuals, she reflected in the work the stages of becoming an emigrant (i.e. shock, suffering, struggling with reality, stabilization), and she referred to her own experiences, which is confirmed in her reminiscence works. Opowieść o cudzoziemcach belongs to a circle of literature that preserves the history of Polish exile. The autobiographical motifs present in the poem, as well as the combination of the individual perspective with the collective experience, allowed the writer to reflect not only the realities faced by Polish emigrants, but above all to draw a portrait of their souls torn by a longing for their homeland.